Development of carbon-based material from biomass for the removal of Ni2+ and CO2 from fluid phase. (December 2018) - Mathangi, J.B.; Sadeesh Sharma, M.; Mercy Jacquline, B.; Helen Kalavathy, M.
Abstract: Adsorption technique was employed to reduce the pollutants from the fluid phase. In this research work, Activated Carbon was produced by chemical activation of wood sawdust at different impregnation ratios and the yield, bulk density, methylene blue number, iodine number and pH point of zero charges were determined. The SBET for AC3H was found to be 797.73 m 2  g −1 . Batch adsorption for the removal of nickel was carried out to perform the isotherm and kinetic study by varying parameters such as contact time, initial metal ion concentration, carbon dosage and temperature. The maximum adsorption capacity of Ni 2+ onto adsorbent was 16.47 mg g −1 . The fixed bed adsorption was performed for parameters such as particle size of 1.7 mm, 1.4 mm & 0.6 mm and flow rate of 50 mL min −1, 70 mL min −1 and 90 mL min −1 which in turn indicated favorable column dynamics and its CO2 adsorptive behavior. The maximum equilibrium adsorption capacity for CO2 adsorption obtained was 0.96 mol kg −1 for the flow rate of 90 mL min −1 and a particle size of 0.6 mm. Kinetic and dynamic models were fitted with the experimental data and the adsorption constants were determined. Highlights: A novel low cost adsorbent that represents green technology for pollution treatment. AC was prepared from WSD by chemical activation. AC3H can be used for the treatment of fluid phase pollutants. Nickel and Carbon dioxide adsorptive behavior studied. Isotherm, kinetic, dynamic models determined.